2015
DOI: 10.1007/s11829-015-9398-4
|View full text |Cite
|
Sign up to set email alerts
|

How many species of arthropods visit flowers?

Abstract: The majority of living plant species are pollinated by insects, and this interaction is thought to have played a major role in driving the diversification of modern angiosperms. But while flower-insect interactions have been well studied from the perspective of plants in the form of pollination biology, few studies have been carried out from an entomological perspective, where flowers are resources to exploit. As a consequence, it remains unknown how many insect species actually utilise floral resources, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 185 publications
1
96
0
7
Order By: Relevance
“…The last known report by Schuster (1974) listed merely seven orthopteran species visiting six flowers from Peru and Panama from two years of sampling which may also have underestimated the diversity of flower-visiting orthopterans. Wardhaugh (2015) suggested that orthopterans are rare flower-visitors but we showed that there are more flower-visiting species than previously known.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…The last known report by Schuster (1974) listed merely seven orthopteran species visiting six flowers from Peru and Panama from two years of sampling which may also have underestimated the diversity of flower-visiting orthopterans. Wardhaugh (2015) suggested that orthopterans are rare flower-visitors but we showed that there are more flower-visiting species than previously known.…”
Section: Discussionmentioning
confidence: 48%
“…Orthopterans are only some of the many invertebrates that visit flowers (Wardhaugh 2015). To our best understanding, we provide here the first documentation of flower-visiting orthopterans from Southeast Asia and the most extensive one from the tropical region.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…All dandelion microspecies included in this study were apomictic; therefore, pollination is not important for their life cycle. This specifi c fact deserves to be accentuated because pollination is an important facet of plant-insect relationships, and one of the factors driving their co-evolution (Schiestl & Johnson, 2013;Wardhaugh, 2015).…”
Section: Byturusmentioning
confidence: 99%